Survey of the Use of the System for Separate Collection of Household Waste from Packaging in the Municipality of Stara Zagora - Getzova, Viktoriya; Berberova, Ralitza (Annual of Natural Sciences Department, 2021)
Separate waste collection and recycling are at the basis of todayâ€™s waste management. This helps the reduction of landfilled waste, which aims to reduce soil, water, and air pollution, on the one hand, and to cut down on the depletion of resources for new production, on the other. A large portion of household waste comes from the so-called â€œwidespread wasteâ€, which includes packaging waste. Legislation at European and national levels sets specific goals to overcome this problem. Separate waste collection is carried out by municipalities via waste recycling companies, which set up and operate systems for separate collection. Citizens are at the heart of the efficient functioning of these systems. A separate waste collection system of this kind has been established in the municipality of Stara Zagora in Bulgaria. The objective of this paper is to present the results of a questionnaire survey of the systemâ€™s users to establish their awareness and attitudes regarding the process of separate waste collection. The results can be used to improve the system.